hucMSCs Attenuate IBD through Releasing miR148b-5p to Inhibit the Expression of 15-lox-1 in Macrophages - Jingjing Kang; Zhaoyang Zhang; Jingyan Wang; Gaoying Wang; Yongmin Yan; Hui Qian; Xu Zhang; Wenrong Xu; Fei Mao (Hindawi Limited, 2019)
Mesenchymal stem cells (MSCs) exert powerful immunosuppression in inflammatory bowel disease (IBD). Macrophages are the dominant inflammatory cells in enteritis regulated via MSCs. However, the roles of macrophages in the process of MSCs attenuating IBD and the mechanisms of MSCs regulating macrophages are largely unknown. In this study, DSS- (dextran sulfate sodium salt-) induced IBD in macrophage-depleted models of CD11b-DTR mice was used to study the relationship between hucMSCs (human umbilical cord mesenchymal stromal cells) and macrophage. Body weights, disease activities, and pathological changes were documented to assess the therapeutic effects of hucMSCs. Furthermore, hucMSCs transfected with miR148b-5p mimics and miR148b-5p inhibitors were cocultured with LPS-induced RAW264.7 cells to investigate the role of miR148b-5p in hucMSC-regulated colitis. The outcome indicated that hucMSCs attenuated the IBD by downregulating 15-lox-1 expression in macrophages. Further findings pointed out that hucMSCs transfected with miR148b-5p mimics could be elevated to promote the tissue repair and inhibit the expression of 15-lox-1 but failed to perform the function of easing enteritis when treated with miR148b-5p inhibitors. In conclusions, we propose that hucMSCs attenuate IBD by releasing miR148b-5p to inhibit the expression of 15-lox-1 in macrophages.